Generation of functional hepatocytes by forward programming with nuclear receptors - Rute A Tomaz; Ekaterini D Zacharis; Fabian Bachinger; Annabelle Wurmser; Daniel Yamamoto; Sandra Petrus-Reurer; Carola M Morell; Dominika Dziedzicka; Brandon T Wesley; Imbisaat Geti; Charis-Patricia Segeritz; Miguel C de Brito; et al. (eLife, 2022)
Production of large quantities of hepatocytes remains a major challenge for a number of clinical applications in the biomedical field. Directed differentiation of human pluripotent stem cells (hPSCs) into hepatocyte-like cells (HLCs) provides an advantageous solution and a number of protocols have been developed for this purpose. However, these methods usually follow different steps of liver development in vitro, which is time consuming and requires complex culture conditions. In addition, HLCs lack the full repertoire of functionalities characterising primary hepatocytes. Here, we explore the interest of forward programming to generate hepatocytes from hPSCs and to bypass these limitations. This approach relies on the overexpression of three hepatocyte nuclear factors (HNF1A, HNF6, and FOXA3) in combination with different nuclear receptors expressed in the adult liver using the OPTi-OX platform. Forward programming allows for the rapid production of hepatocytes (FoP-Heps) with functional characteristics using a simplified process. We also uncovered that the overexpression of nuclear receptors such as RORc can enhance specific functionalities of FoP-Heps thereby validating its role in lipid/glucose metabolism. Together, our results show that forward programming could offer a versatile alternative to direct differentiation for generating hepatocytes in vitro.